2022
DOI: 10.1155/2022/4109070
|View full text |Cite
|
Sign up to set email alerts
|

Federated Learning for Supply Chain Demand Forecasting

Abstract: With the country’s policy support and the rapid development of Internet technology, the domestic consumption level has been escalating and the consumption structure has changed. The traditional retail industry cannot integrate all the relevant data due to data security and privacy protection concerns so that it is unable to adjust sales strategies in an accurate and timely manner. New retail has sounded the clarion call for the retail revolution. The supply chain demand forecasting is an important problem for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…To this end, FRSs can allow different data sources to collaborate in order to provide personalized recommendations to customers. A literature review on the application of FRSs in E-commerce revealed the various advantages [179][180][181]. First, FRSs can help reduce the cost of data access and storage.…”
Section: E-commercementioning
confidence: 99%
“…To this end, FRSs can allow different data sources to collaborate in order to provide personalized recommendations to customers. A literature review on the application of FRSs in E-commerce revealed the various advantages [179][180][181]. First, FRSs can help reduce the cost of data access and storage.…”
Section: E-commercementioning
confidence: 99%
“…Wang et al [8] introduced a framework for forecasting commodity demand in the retail supply chain. Their approach leverages vertical federated learning to address data security and privacy concerns in the context of new retail.…”
Section: Related Workmentioning
confidence: 99%
“…The introduction of human-level intelligence AGI has the potential to provide far greater levels of automation than presently possible, including tasks performed by highly educated individuals, such as researchers (Müller and Bostrom, 2016). Combining AI and big data (Duan et al ., 2019) carries further potential, leading to integrated supply and demand forecasting (Wang et al ., 2022) with anticipated customer demands met by automatically regulated supply chains. Hyperautomation will continue to enable machines to complete a growing proportion of tasks over the next 100 years but the fear of human obsolescence stemming from the Luddites of the first industrial revolution remains (Conniff, 2011) despite the short-term job creation predictions of 12m by 2025 (World Economic Forum, 2023).…”
Section: Future 100 Yearsmentioning
confidence: 99%